Evaluation and Validation of Different Integrated Pest Management Modules for Field Pea - Chauhan, J. V.; Panickar, Bindu K.; Prajapati, A. R.; Gothi, H. R.; Padhiyar, B. M. (International Journal of Bio-resource and Stress Management, 2025)
This research was carried out during rabi (November-March) 2020–21 at Agronomy Instructional Farm, S. D. Agricultural University, Sardarkrushinagar, Gujarat, India to evaluate the efficacy of seven different Integrated Pest Management (IPM) modules against insect-pests of field pea. Five IPM modules were tested for their efficacy against insect-pest. The result revealed that the module M4 (Border crop with chickpea+treating seeds by imidacloprid 600FS @ 3 ml kg-1 seed+yellow sticky trap @one module-1+sprays of azadirachtin 1500 ppm @ 40 ml 10 l-1 water+HaNPV 250 LE @ 10 ml 10 l-1 of water+profenophos 50 EC @ 10 ml 10 l-1 water) exhibited significantly minimum population of 1.47 aphid 10 cm-1 shoot, 1.00 leafhopper trifoliate-1, 0.62 whitefly trifoliate-1, 0.08 larva plant-1 with lowest pod borer damage (0.30%) and thus proved to be most effective module which was at par with module M1. The highest field pea seed yield (1250 kg ha-1) was also harvested from module M4. The maximum (42.04%) increase in yield was obtained in the plots framed with M4 followed by module M1. The avoidable losses in field pea yield were minimum (9.36%) in module M1. The highest (`Rs. 87,500 ha-1) gross realization was obtained from the plots framed with module M4. The highest Protection Cost: Benefit Ratio (PCBR) was obtained in module M4 (1:3.56) which clearly indicated that module M4 was also the most economical module amongst all.